Role of Radiotherapy in Oncologic Emergency - Sebastian, Andreas Ronald Barata; Jayalie, Vito Filbert; Hanifah, Rizka; Adham, Marlinda; Munandar, Arie (PERHATI-KL, 2023)
Background: Oncologic emergencies often occur in patients who have metastases. This condition requires a prompt and accurate diagnosis. Radiotherapy (RT) plays a substantial role in palliative aspect with the aim of reducing tumor size, reducing symptoms, and improving quality of life. Purpose: To discuss the role of radiotherapy in an oncologic emergency. Literature review: The most common cases requiring radiation in emergency management are superior vena cava syndrome, acute airway obstruction, uncontrolled tumor bleeding, spinal cord compression due to malignancy, and brain metastases. The selection of radiation dose and techniques may vary, taking into consideration patient factors such as poor general condition, the likelihood of receiving curative treatment afterward, severe comorbidities, tumor factors such as histology of malignancy, whether it is a metastatic disease or not, therapeutic factors such as previous radiation history and response to previous systemic therapy. Conclusion: Radiotherapy plays a significant role in oncologic emergency, particularly to reduce symptoms and improve quality of life. Several considerations should be evaluated before determining the appropriate radiation treatment are patient factors, previous radiation therapy and response to previous systemic therapy.